The dawn of everything?. Issue 1 (1st February 2022) - Appadurai, Arjun
Abstract : The Dawn of Humanity is a sweeping account of how the human species adopted agriculture, central bureaucracies, and inequality despite numerous early experiments with other modes of subsistence, high degrees of freedom from hierarchical power, and many examples of egalitarian social organization. The problem, as the author of this guest editorial sees it, is that the historical examples in the book are chosen without an eye for falsification, the main question about the origins of bureaucracy is evaded, and early human societies end up looking suspiciously like the authors' own preferred anarchist idea of the best possible world.